Shaping PEDOT nanoparticles for use in 3D tissue phantoms. Issue 18 (21st January 2016) - Wailes, Elizabeth M.; MacNeill, Christopher M.; McCabe, Eleanor; Levi‐Polyachenko, Nicole H.
ABSTRACT: Controlling the relative concentrations of surfactant, oxidant iron (III) chloride, 3, 4‐ethylenedioxythiophene (EDOT) monomer in water, and mechanical influences such as sonication and stirring, resulted in the synthesis of PEDOT nanoparticles with various dimensions and aspect ratios. Having a ratio of two or more of surfactant compared to the oxidant led to a greater yield of thinner nanofibers, as did utilizing a more dilute concentration of the reactants. These nanoparticles were shown to be cyto‐compatible in 3D culture for both human and mouse cells. The key feature is that PEDOT nanoparticles with a variety of morphologies can be obtained using water only without the need for hexanes in the procedures. The synthesized PEDOT nanoparticles absorb light across the infrared spectrum and in turn are capable of generating heat for biologically relevant studies of hyperthermia in three dimensional tissue phantoms. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43378. Abstract :